Creative Artificial Intelligence: Generation of New Objects - Rivera, Selva Soledad (2023)
This paper presents an introduction to Artificial Intelligence and creativity. Creativity is analyzed from a biological point of view based on the concept of neuroplasticity of the human brain. It seeks to understand the process associated with the creative act to formalize it. He analyzes biological neural networks not from the point of view of their topology, but from the process, they carry out during the creative process.The focus of attention is placed on the generation of new objects. It seeks to formalize the creative act to propose a model of creativity with the ultimate goal of building a Creative Artificial Intelligence. To understand this process, well-documented examples from real life were studied. From them, the creativity process is analyzed and deconstructed into basic elements to later formalize it.Throughout history, various authors have studied the creative act and this has given rise to different theories. The proposed model is analyzed taking into account traditional approaches, constituting a tool for technological improvement that will complement human creativity.